Entrepreneurship, Local Growth and Global Markets - Giuseppe Cappiello (Symphonya, 2016)
The creation or start-up of new companies has been the subject of extensive discussion in recent years, both at a scientific and a political level.  The reason for this lies primarily in the hope that new businesses will contribute to local development and employment. The birth of new businesses concerns three dimensions: the subjective one, the context in which the company was founded and the strategic choices made. These choices are particularly useful in understanding that an organic, all-encompassing design is required, especially if a global ecosystem is involved.  At the same time, it seems necessary for the State to play an enabling role.